Problems of Mudharabah Financing in Islamic Banking After the Implementation of Qanun of Islamic Financial Institutions in Aceh - Yusmalinda Yusmalinda; Asmuni Asmuni; Dhiauddin Tanjung (Justicia Islamica, 2022)
The mudharabah contract has become one of the Islamic banking products legitimated by The National Sharia Board and Financial Services Authority. The Aceh government, through the Qanun of Islamic Financial Institutions, has emphasized that banking practices in Aceh must rely on sharia principles. The consequence of this regulation is that banks are only allowed to use sharia contracts in every financial and financing transaction. This research is an empirical juridical study with a sociological and normative approach. This approach was employed to analyze the use of mudharabah contracts from both practical and theoretical aspects. The results of this study indicate that although the mudharabah contract has been designated as one of the financing products in Islamic banking, the mudharabah contract is not fully applied for financing. The mudharabah contract is only implemented for corporate purposes, not for small traders. This is due to several things, including the high risk in mudharabah financing, low bank confidence in customers, fluctuating profits, and low-risk management. This study aims to analyze the problems of mudharabah financing after implementing the 2018 Qanun of Islamic Financial Institutions in Aceh. The results of this study can answer the main problems in the mudharabah contracts. Thus the mudharabah contract can be optimized in the financing system of Islamic banking in Aceh. Akad mudharabah sudah menjadi salah satu produk perbankan syariah yang mendapatkan legitimasi dari DSN-MUI dan OJK. Pemerintah Aceh melalui qanun lembaga keuangan syariah telah menegaskan bahwa praktik perbankan di Aceh harus menggunakan prinsip-prinsip syariah. Konsekuensi dari peraturan tersebut yaitu pihak perbankan hanya dapat menggunakan akad bernuansa syariah dalam setiap transaksi keuangan dan pembiayaan. Penelitian ini merupakan kajian yuridis empiris dengan pendekatan sosiologi dan normatif. Pendekatan ini digunakan untuk menganalisis penggunaan akad mudhrabah baik dari aspek praktik dan teoritis. Hasil penelitian ini menunjukkan bahwa, meskipun akad mudharabah telah ditetapkan sebagai salah satu produk pembiayaan pada perbankan syariah, namun nyatanya akad mudharabah tidak sepenuhnya di gunakan dalam pembiayaan, akad mudharabah hanya digunakan untuk korporasi saja, tidak untuk pedagang kecil dan UMKM. Hal ini disebabkan oleh beberapa hal; pertama, tingginya resiko dalam pembiayaan mudharabah; kedua, rendahnya kepercayaan perbankan terhadap nasabah; ketiga, keuntungan yang fluktuatif; keempat, lemahnya manajemen resiko. Penelitian ini berkontribusi untuk mengatasi persoalan pembiayaan mudharabah pasca penerapan qanun lembaga keuangan syariah tahun 2018 di Aceh. Sehingga dengan hasil penelitian ini dapat menjadi jalan keluar terhadap permasalahan utama dalam akad mudharabah, dan akad mudharabah dapat dioptimalkan dalam sistem pembiayaan pada perbankan syariah di Aceh.